2014
DOI: 10.1016/j.egypro.2014.10.198
|View full text |Cite
|
Sign up to set email alerts
|

Novel System for Distributed Energy Generation from a Small Scale Concentrated Solar Power

Abstract: The present work describes the realization of a modular 1-3 kWe, 3-9 kWth micro Combined Heat and Power (m-CHP) system based on innovative Concentrated Solar Power (CSP) and Stirling engine technology. The cogeneration of energy at distributed level is one of leading argument in large part of energy policies related to renewable energy resources and systems. This CSP m-CHP will provide electrical power, heating and cooling for single and multiple domestic dwellings and other small buildings.The developed syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Concentrating thermal collectors based systems. Crema et al [60][61][62] presented the numerical and experimental study of a modular mCHP plant producing 1-3 kW electrical power and 3-9 kW thermal power using parabolic trough collectors with evacuated tube receivers and a Stirling engine. The plant was designed to provide electricity, heating, and cooling to single and multiple dwellings and other small buildings.…”
Section: Solar Thermal Based Systemsmentioning
confidence: 99%
“…Concentrating thermal collectors based systems. Crema et al [60][61][62] presented the numerical and experimental study of a modular mCHP plant producing 1-3 kW electrical power and 3-9 kW thermal power using parabolic trough collectors with evacuated tube receivers and a Stirling engine. The plant was designed to provide electricity, heating, and cooling to single and multiple dwellings and other small buildings.…”
Section: Solar Thermal Based Systemsmentioning
confidence: 99%
“…Also, many types of research have been done for developing the model of small-scale solar thermal trigeneration plants consisting parabolic trough collectors and ORC units [93][94][95][96][97][98]. In 2014, a concentrated solar combined heat and power plant scheme was presented by Han et al [21].…”
Section: Concentrating Solar Thermal Collectorsmentioning
confidence: 99%
“…The output of this article demonstrated that the performance of the expander isentropic was satisfactory, and it could be enhanced by changing some mechanical parts. The total produced energy of the proposed configuration was 1710 kWh.Crema et al[94] assessed the integration of evacuated tubes to a micro-CHP configuration, composed of CSP and Stirling engine system, in building sector. The proposed combination was satisfying in supplying the demands of the buildings.…”
mentioning
confidence: 99%
“…For the production of heat at a medium temperature, 150-250 • C, solar collectors could be smaller with respect to the usual PTCs employed in the large high-temperature plants [1][2][3][4]. The advantage of having reduced dimensions permits to install these solar collection systems in small areas or even on building roofs [5][6][7][8]. The examined micro-PTC (m-PTC) is ten times smaller than a common PTC.…”
Section: Introductionmentioning
confidence: 99%